Optimizing daylighting and passive thermal comfort in office buildings: - Muhammad Aminu Musa (Civil Engineering Dept, Balikpapan State Polytechnics, 2026)
There is disagreement among numerous researchers regarding sustainable office building design especially for the ideal values of Daylighting and Passive Indoor Thermal Comfort (DPITC) in tropical countries like Nigeria. The study aims to develop a framework for a sustainable office building for optimum daylighting and passive indoor thermal comfort (DPITC) in the temperate dry climate of Nigeria. Using a quantitative experimental design with OpenStudio 3.3.0 simulation tools, the study compared closed-plan (double-banked) and open-plan office building prototypes in Jalingo, Zaria, and Abuja from January to December 2024. The open-plan design demonstrated statistically significant superiority over closed-plan designs across key metrics: Daylight Autonomy (45.7%, p < .0001), Useful Daylight Illuminance (55.2%, p < .0001), Spatial Daylight Autonomy (55.2%, p < .0001), and Relative Humidity (10.6%, p < .0001). Multiple regression analysis yielded a predictive equation: A = 170.87 - 512.232WWR + 49.41PF - 8.6R, enabling architects to optimize orientation (A), window-to-wall ratio (WWR), overhang projection factor (PF), and wall R-values for DPITC. The framework provides evidence-based guidance for sustainable office design in Northern Nigeria's temperate dry climate. Findings support the hypothesis that mean effects of DPITC are significantly different for at least one of the azimuths, WWR, overhang projection factors, and R-values of external wall materials in open-plan office buildings in this climate zone.